Sensitivity and specificity of bedside ultrasonography in the diagnosis of fractures of the fifth metacarpal. Issue 3 (23rd October 2013) - Aksay, Ersin; Yesilaras, Murat; Kılıc, Turgay Yılmaz; Tur, Feriyde Calıskan; Sever, Mustafa; Kaya, Ahmet
Abstract : Objectives: Ultrasonography is becoming increasingly common in the diagnosis of fracture in emergency medicine. The aim of our study was to investigate the diagnostic accuracy of sonographic examinations for diagnosing fifth metacarpal fractures. Methods: A prospective study was performed of consecutive patients aged >14 years admitted to the emergency department with hand trauma and tenderness over the fifth metacarpal. Anteroposterior and oblique plain x-rays were taken on all patients. Emergency physicians performed bedside sonographic examination. The x-rays were reported by an orthopaedic surgeon who was blinded to the sonographic examination findings. The orthopaedic surgeon's report was considered the gold standard unless a CT scan was performed. In the single case where this occurred, the CT scan report was considered the gold standard. Results: Eighty one patients were included in the study, 39 of whom had fractures. Sonographic examination identified the fractures in 38 patients. One occult fracture undetected by plain radiography, later shown on CT scan, was identified by sonographic examination. There were three cases with false positive ultrasound findings. The sensitivity of the diagnosis of fifth metacarpal fractures by ultrasonography was 97.4% (95% CI 84.9% to 99.9%), specificity was 92.9% (95% CI 79.4% to 98.1%), positive likelihood ratio (LR) was 14 (95% CI 4.58 to 41), negative LR was 0.03 (95% CI 0.00 to 0.19), negative predictive value was 97.5% (95% CI 85.3% to 99.9%) and positive predictive value was 92.6% (95% CI 79% to 98.1%). Conclusions: Sonographic examination can be used as an effective diagnostic tool in patients with fifth metacarpal trauma.